Late Embryogenesis Abundant (LEA)5 Regulates Translation in Mitochondria and Chloroplasts to Enhance Growth and Stress Tolerance - Karpinska, Barbara; Razak, Nurhayati; Shaw, Daniel S.; Plumb, William; Van De Slijke, Eveline; Stephens, Jennifer; De Jaeger, Geert; Murcha, Monika W.; Foyer, Christine H. (Frontiers in Plant Science, 2022)
The late embryogenesis abundant (LEA)5 protein is predominantly expressed in Arabidopsis leaves in the dark, the levels of LEA5 transcripts decreasing rapidly upon illumination. LEA5 is important in plant responses to environmental stresses but the mechanisms involved have not been elucidated. We therefore explored LEA5 functions in Arabidopsis mutants (lea5) and transgenic Arabidopsis plants constitutively expressing LEA5 (OEX 2-5), as well as in transgenic barley lines expressing the Arabidopsis LEA5 gene. The OEX 2-5 plants grew better than controls and lea5 mutants in the presence of the prooxidants methyl viologen and menadione. Confocal microscopy of Arabidopsis mesophyll protoplasts expressing a LEA5-YFP fusion protein demonstrated that LEA5 could be localized to chloroplasts as well as mitochondria in Arabidopsis protoplasts. Tandem affinity purification (TAP) analysis revealed LEA5 interacts with the chloroplast DEAD-box ATP-dependent RNA helicase 22 (RH22) in Arabidopsis cells. Split YFP analysis confirmed the interaction between RH22 and LEA5 in chloroplasts. The abundance of translated protein products in chloroplasts was decreased in transgenic Arabidopsis plants and increased in lea5 knockout mutants. Conversely, the abundance of translated mitochondrial protein products was increased in OEX 2-5 plants and decreased in lea5 mutants. Mitochondrial electron transport rates were higher in the OEX 2-5 plants than the wild type. The transformed barley lines expressing the Arabidopsis LEA5 had increased seed yields, but they showed a greater drought-induced inhibition of photosynthesis than controls. Taken together, these data demonstrate that LEA5 regulates organellar translation, in order to enhance respiration relative to photosynthesis in response to stress.